Vietnamese mother's conceptions of childhood overweight: findings from a qualitative study - Loan Minh Do; Viveca Larsson; Toan Khanh Tran; Huong Thanh Nguyen; Bo Eriksson; Henry Ascher (Taylor & Francis Group, 2016)
Background: Childhood overweight and obesity is a new and emerging problem in Vietnam. The so far observed prevalence increases have pointed to the need for public health intervention strategies with parents as crucial resources for change. Objective: The aim of this study was to understand mothers' conceptions of childhood overweight. Design: Four focus group discussions were conducted with a total of 33 mothers of preschool children, 4-6 years old, living in urban and rural districts of Hanoi, Vietnam. The discussions were audio taped and transcribed verbatim. The obtained data were analyzed using the principles of phenomenography. Results: Four main categories with 13 subcategories emerged in the process of analysis. The first category, called 'Concept of overweight', contained mothers' views on childhood overweight. A major concern was the negative aspects of overweight such as impaired social interaction and health problems. The second category, 'Identification of overweight', described the ways mothers use to recognize overweight in children: own experience, growth chart, and public or health care system's information. The third category, 'Causes of overweight', showed mothers' understanding of factors possibly contributing to overweight development: unhealthy food and lifestyle, genetic susceptibility, parent's lack of knowledge, and limited time to take care of children as well as economic improvement. The fourth category, 'Management of overweight', described the ways mothers use to manage a child's weight problem: control of their food intake, increasing their physical activity, and encouraging their child self-control. However, they find such strategies difficult to implement and their intentions are sometimes challenged by the child's grandparents. Conclusions: The study gives an understanding of the mothers' conceptions of four important and practically useful aspects of overweight in children. The findings highlight the roles of media and the health care system in enhancing a social awareness of the problem and the need for prevention. Growth charts need to be used more regularly and consciously in child health care for early detection of children at risk and as a tool for information to parents. When designing intervention programs, the entire extended families, especially grandparents and their roles, need to be considered.